Self- perceived stress in relation to anxiety, depression and health-related quality of life among health professions students - Račić, Maja (Zdravstveno varstvo, 2017)
Introduction. The purpose of the present study was to examine self-perceived stress of health professions students at the Faculty of Medicine Foča, and to explore its association with anxiety, depression and health- related quality of life. Methods. The cross-sectional study enrolled 451 students at the Faculty of Medicine (medicine, dentistry, nursing and speech therapy). Survey instruments were distributed at the conclusion of the spring semester during the last required lecture for each year and study programme class. Perceived stress was assessed using the 14-item Perceived Stress Scale. The students were evaluated for symptoms of depression and anxiety, using Zung%s self-assessment inventory for depression and the Spielberger State-Trait Anxiety Inventory (STAI). European Quality of Life-5 dimensions were used for describing and evaluating health. Multivariate analyses were carried out using logistic regression to examine the relationship between the outcome variable and selected determinant factors. Results. A high degree of stress was reported by 1.6% of students, while the majority of students had either moderate (70.6%) or low degree (27.5%) of stress. The significant independent factors associated with perceived stress were anxiety score (OR, 0.339; CI 95%, 0.276-0.403) and EQ-5D score (OR, 0.044; CI 95%, 0.033-0.085). A high degree of perceived stress (OR, 0.624; CI 95%, 0.507-0.704), the presence of depression (OR, 0.800; CI 95%, 0.513-1.087), and low quality of life were associated with anxiety (OR, 0.073; CI 95%, 0.018-0.128). Conclusion. Higher levels of perceived stress predispose health professions students for anxiety and lower quality of life. The study programme was not a significant determinant of perceived stress sore.
Keywords: anksioznost; anxiety; assessment; BiH; kakovost življenja; ocena; quality of life; standard of living; stres; stress; student; students; študenti